A didactic model for competences building in sport games (2013)
RESUMEN: Introduction. Several Studies in sports games found that the best players have larger quantity of declarative and procedural knowledge (Ericsson et. al., 1993), some authors (Pellegrino, 1998; Eysenback; Keane, 2000) refer to the extension of acquired knowledge as the fundamental difference between experts and novices. Up on this knowledge, the experts are capable of collect the most relevant information from the environment and to make the appropriate decisions to meet the specific requirements of the current situation. The experts seem to bear the necessary knowledge to carry out effective decision making processes to succeed. This knowledge is acquired on the base of a long period of intentional practice (Deakin; Cobley, 2003).